Pengaruh Model Pembelajaran Talking Stick terhadap Kepercayaan Diri Siswa pada Mata Pelajaran Geografi Kelas X SMAN 1 Srengat Blitar - Shiera Nada Nasuha; Bagus Setiawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aimed to determine the effect of talking stick learning model on students' self-confidence in geography class X SMAN 1 Srengat Blitar. This study used a quantitative approach of quasi-experimental design with nonequivalent control group design. The sample in this study was selected using purposive sampling technique with 34 students in the control class and 34 students in the experimental class. The data in this study were obtained through the results of students' self-confidence questionnaire scores which were analyzed by the Independent Sample T-test and Effect size test. From the results of this study, it can be seen that the talking stick learning model has an effect on student confidence as evidenced by the acquisition of a sig (2-tailed) value of 0.000 <0.05. This study shows that the implementation of the talking stick model can increase students' active participation in learning which can then increase students' self-confidence.